2007
DOI: 10.1373/clinchem.2007.074401
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Response by Ficolin Binding in Apoptotic Placenta Is Associated with the Clinical Syndrome of Preeclampsia

Abstract: Background: Unidentified circulating factors derived from placenta are thought to be responsible for the exaggerated systemic inflammation leading to preeclampsia. Our aim was to identify the circulating factors present in preeclampsia and to investigate their relationship to the underlying systemic immune response responsible for the associated clinical manifestations. Methods: We obtained blood samples from pregnant women with and without preeclampsia and performed comparative proteomic analyses to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
45
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 27 publications
2
45
0
2
Order By: Relevance
“…It has also been shown that high pretransplant levels of ficolin-3 are associated with kidney graft survival [29]. Ficolin-3 appears to be consumed in preeclampsia and binds to apoptotic placentas [30]. Moreover, ficolin-3 has been shown to be decreased in patients with diabetic nephropathy [31], and that it varied significantly between type 2 diabetes patients and controls [32].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that high pretransplant levels of ficolin-3 are associated with kidney graft survival [29]. Ficolin-3 appears to be consumed in preeclampsia and binds to apoptotic placentas [30]. Moreover, ficolin-3 has been shown to be decreased in patients with diabetic nephropathy [31], and that it varied significantly between type 2 diabetes patients and controls [32].…”
Section: Discussionmentioning
confidence: 99%
“…Ficolin-3 may also play a major role in the development of GDM. Moreover, ficolins are probably responsible for the clinical manifestations of PE and may also have therapeutic potential to alleviate the adverse clinical outcomes and predictive value of this gestational complication [32]. Interestingly, SFRP4 and ficolin-3 initially increased during the second-trimester of pregnancy and then declined before delivery of all the subjects in the present study.…”
Section: Discussionmentioning
confidence: 44%
“…These models enable parallel proteomic and metabolomic investigation, and preliminary work has demonstrated that several metabolites also differed in the culture medium from placental explants cultured in 1% compared with 6% and 20% O 2 . 53 MS-based approaches have also been used to directly investigate pre-eclampsia [54][55][56] and preterm labour. 57,58 For this purpose, biological samples from primary cultured trophoblast, 55 placental membranes, 57 amniotic fluid, 56,59 maternal blood 54 and vaginal fluid 58 have been analysed using several different techniques.…”
Section: Discussionmentioning
confidence: 99%
“…57,58 For this purpose, biological samples from primary cultured trophoblast, 55 placental membranes, 57 amniotic fluid, 56,59 maternal blood 54 and vaginal fluid 58 have been analysed using several different techniques. To date, the majority of research has focused on pre-eclampsia; this has included observations demonstrating altered levels of ficolins (associated with the induction of innate immunity) in the plasma of women with established disease, 54 the differential expression of seven proteins from placental trophoblasts between women with normotensive pregnancies and women with pre-eclampsia 55 and the increase of the monomeric form of transthyretin (a transport protein for thyroxine and retinol-binding protein) in the amniotic fluid of five women with pre-eclampsia in comparison to women with normal outcome pregnancies, 56 In relation to preterm labour, the differential expression of 11 proteins identified in placental tissue and membranes between women with preterm labour and those with normal outcome pregnancies has been observed, 57 and 28 proteins identified in cervical-vaginal fluid demonstrate differences in comparisons of women experiencing preterm labour with those progressing to term. 58 Although these studies demonstrate the applicability of omic techniques to pregnancy complications, so far, limited conclusions can be drawn as time-of-disease samples have been used, and future work needs to concentrate on samples taken earlier in pregnancy.…”
Section: Discussionmentioning
confidence: 99%